Examining The Relationship Between Dividend Policy and Stock Price Movements - Nofryanti, Nofryanti; Narendro, Wika Nandayana; Salsabila, Jihan Qanita (The Future of Education Journal, 2026)
This study examines and summarizes the relationship between dividend policy and stock price movements in the consumer non-cyclicals sector. The research aims to determine whether dividend policy contributes to investor confidence and influences stock price behavior. The study employs a panel data approach with a two-year observation period (2023–2024) and uses purposive sampling to select 26 companies listed on the Indonesia Stock Exchange. Descriptive statistical analysis is applied to capture variations in stock prices and dividend payout ratios. This research adopts a quantitative descriptive approach, which systematically and structurally describes relevant phenomena and characteristics based on numerical data. The findings indicate that a high Dividend Payout Ratio (DPR) is not necessarily accompanied by an increase in stock prices. This result suggests that investors’ decisions in valuing company shares are not solely influenced by the magnitude of dividends distributed, but also by other fundamental and market-related factors.